ON THE PECULIARITIES OF THE FORMATION OF ANALYTICAL THINKING AMONG FUTURE RUSSIAN PHILOLOGISTS - Madyarova Nasiba Adkhamovna (Western European Studies, 2024)
Modern society requires an analytically thinking teacher who is able to instill analytical skills in his/her students; therefore, when preparing future teachers, in particular teachers of Russian literature, it is important to develop their analytical thinking. One of the ways of its formation can be the ability to work with didactic material, to choose the best textbooks for teaching certain lexical and grammatical topics.
Keywords: analysis; analytical thinking; incomplete sentences